Faktor-Faktor Yang Mempengaruhi Kepatuhan Pelaporan Wajib Pajak Orang Pribadi - Neni Marlina Br Purba; Dian Efriyenty (AKUNTANSI DEWANTARA, 2021)
Tax reporting is the responsibility of taxpayers after making tax payments. The mismatch between the number of registered taxpayers and the number of taxpayers who report taxes is a separate problem for the government in managing the tax results received. Where the number who report taxes is very small compared to the number of registered taxpayers. Based on these problems, the purpose of this study is to determine the factors that influence individual taxpayer reporting compliance. The population used by all individual taxpayers who are registered at KPP Pratama Batam Selatan. While the sample was taken through simple random sampling technique with the Slovin formula so that the sample used was 100 respondents. Data analysis techniques are data instrument test, classical assumptions, descriptive analysis and hypothesis testing with the help of SPSS. The results obtained, partially the application of e-filling and tax sanctions has a significant effect on tax reporting compliance while tax awareness and understanding have no significant effect. The f test results show that all the independent variables simultaneously have a significant effect on the dependent variable.